2018
DOI: 10.21134/haaj.v18i2.389
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Expectancy-Adolescent Questionnaire (AEQ-AB): Validation for portuguese college students

Abstract: Excessive alcohol consumption by college students is being recognized more and more, and its negative effects justify the implementation of prevention programs. Positive expectancies of alcohol are frequently acquired in adolescence and assume an important role in young-adult consumption patterns. This paper describes validation of the brief version of the Alcohol Expectancy-Adolescent Questionnaire (AEQ-AB) carried out with a sample of 317 freshman-year college students at a public Portuguese Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The effects of age at first drink and being on the firstchoice degree course were stronger when the indirect effects of positive perceptions were considered. As in previous studies (Almeida et al, 2018;Davoren et al, 2016), older students and those who started drinking alcohol younger reported higher beer consumption.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The effects of age at first drink and being on the firstchoice degree course were stronger when the indirect effects of positive perceptions were considered. As in previous studies (Almeida et al, 2018;Davoren et al, 2016), older students and those who started drinking alcohol younger reported higher beer consumption.…”
Section: Resultssupporting
confidence: 81%
“…No being in a degree of first option can produces less engagement in learning and other academic activities with more participation in social and interpersonal events out campus, namely during night, where the alcohol consumption increases. Not be in a course of first option can increase the alcohol consumption to reduce unpleasant emotions, low perceptions of self-efficacy and meet social support (Almeida et al, 2018;Simões et al, 2018;Wicki et al, 2017). Students not placed in a first option course tend to present more difficulties in their academic adaptation, what appears related to high alcohol consumptions rates (Costa et al, 2017;Davoren et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the beliefs that adolescents have about the consequences of using substances such as alcohol or tobacco are erroneous [14], which is associated with minimizing derived risks [15]. Thus, adolescents with positive attitudes and/or expectations toward the use of alcohol show a higher risk in starting and maintaining use behavior [16][17][18]. In this line, several studies have associated impulsivity and sensation-seeking with drug use [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the beliefs that adolescents have about the consequences of using substances like alcohol or tobacco are erroneous [14], which is associated with minimizing derived risks [15]. Thus adolescents with positive attitudes and/or expectations toward use of alcohol, show a higher risk in starting and maintaining use behavior [16][17][18]. In this line, several studies have associated impulsivity and sensation-seeking with drug use [17,19,20].…”
Section: Introductionmentioning
confidence: 99%